(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2024)
In this article, in the world in the second half of the 20th century, the integration of environmental protection and social economic development will become invisible through the processes of transition from the beginning of understanding of environmental problems on a global scale to the "Path of Sustainable Development". In connection with the theory of environmental problems on our planet, its socio-philosophical problems were also developing. Humanity’s methods of identifying and solving these global problems today and their perspectives are highlighted